2018
DOI: 10.1182/bloodadvances.2018021238
|View full text |Cite
|
Sign up to set email alerts
|

Timing of treatment of smoldering myeloma: delay until progression

Abstract: This article has a companion Point by Mateos and González-Calle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Despite the increasingly strong interest in intervening at the precursor stage for the early interception and prevention of MM, safe and cost-effective interventions are lacking. Although clinical trials have shown that earlier initiation of anti-MM therapies at the precursor stage (eg, lenalidomide-based regimen for high-risk SMM [ 5 ]) may alter the natural disease course and improve survival [ 5 , 6 ], early treatment remains highly controversial due to high costs and toxicity risks to patients, limiting its use to only a subset of patients at the highest risk strata [ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasingly strong interest in intervening at the precursor stage for the early interception and prevention of MM, safe and cost-effective interventions are lacking. Although clinical trials have shown that earlier initiation of anti-MM therapies at the precursor stage (eg, lenalidomide-based regimen for high-risk SMM [ 5 ]) may alter the natural disease course and improve survival [ 5 , 6 ], early treatment remains highly controversial due to high costs and toxicity risks to patients, limiting its use to only a subset of patients at the highest risk strata [ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%